Penguatan Kapasitas Kelompok Tani Dalam Budidaya Porang Berbasis Pertanian Konservasi-Agroforestry Di Desa Sambi Elen, Lombok Utara - Sukartono; Suwardji; Bambang Hari Kusumo; Arifin Aria Bakti; Edwin (Fakultas Pertanian Universitas Mataram, 2020)
Amorphophallus oncophyllus Prain (porang) is a recently introduced commodity as a cultivated plant in Lombok Island. One of the farmer groups that has adopted the porang plant is the Suli Bakong Ganda Farmer Group in Sambik Elen Village, Bayan District, North Lomok. Kelompok Tani are smallholders in agroforestry systems that are not yet agribusiness oriented. The priority issues for strengthening the capacity of farmer groups related to the development of porang as a new source of income are: (i) farmers' limited knowledge of porang cultivation techniques based on conservation agriculture principles, including mastery of nursery techniques (ii) they need good partners for technical assistance for cultivation, access to capital and market partners (iii) they do not fully understand the value added prospects of porang tuber processing. A solution to this problem is urgently needed so that farmer groups are more optimistic about managing porang agroforestry as a new source of sustainable income. Therefore, empowerment activities have been carried out using the “Modified Participatory Research” (MPAR) method through extension activities, training and building independent demonstration plots by applying the principles of conservation agriculture. The achievements of this service were (i) The knowledge of farmer group members on the principles of conservation agriculture in the porang-agroforestry system has increased (85%) and mastery of porang nursery techniques with cut bulbs with mixed potting media (manure and biochar) (ii) Target partners be able to propagate porang seedlings using the cut bulb technique and believe that this technique is effective to be applied (iii) Farmer groups are willing to carry out an independent demonstration plot for the application of conservation agriculture in porang agroforestry land in the rainy season 2020/2021. This area was guided by the Department of Soil Science FP UNRAM as a field laboratory to support the Merdeka Learning-Merdeka Campus (MB-KM) curriculum